The relational calibration of fear. - Harbin, Ami (Synthese, 2022)
In this article, I consider how fear in contexts of crisis shapes and is shaped by agents’ relationships. I survey a number of approaches to understanding fearing at the intersection of empirical psychology and philosophy, highlighting the extent to which interpersonal relationships are positioned as involved in processes of fearing, and establish what I take to insufficient attention paid by these approaches to the ways interpersonal relations shape the emotions we come to have. Contexts of acute crisis and uncertainty can involve rapidly adjusting practices of fearing in response to other agents, both those we trust and those we do not. I call for the development of a model of ‘relational calibration’ for understanding the complex interpersonal dynamics of fearing during crises, including in the context of the COVID-19 pandemic.